Sistem Pendukung Keputusan Mengukur Tingkat Pemahaman Siswa terhadap Pembelajaran dengan Menggunakan Metode Simple Additive Weighting (SAW) - Suherman; Ikna Niswatuzzakiah; Aldi Irawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Education plays a crucial role in developing individual potential. Learning evaluation, particularly in Biology subjects, is essential to comprehensively assess students' understanding. However, traditional evaluations such as mid-term and final exams often overlook the learning process. This study aims to measure the level of understanding of Grade XI Science 1 students at SMA Negeri 3 Pandeglang on the topics of Human Reproduction and the Immune System using the Simple Additive Weighting (SAW) method. This method was chosen due to its capability in determining the weight of criteria and ranking alternatives. The indicators of student understanding in this study include the ability to recall, elaborate, summarize, provide examples, and draw conclusions. The results indicate that 86.11% of students fall into the "very understanding" category regarding the taught materials. The system was developed using the CodeIgniter framework, PHP programming language, and MySQL database. The findings are expected to assist teachers in formulating more effective teaching strategies and providing objective evaluations of student comprehension.